Vitexin promotes nitric oxide production in human umbilical vein endothelial cells - Azizah Ugusman; Izzat Zulhilmi Abd Rahman; Nina Diyana Rusanuar; Amilia Aminuddin; Adila A Hamid (Penerbit Universiti Kebangsaan Malaysia, 2025)
Endothelial nitric oxide synthase (eNOS) plays a pivotal vasculoprotective role by synthesising nitric oxide (NO), a vital anti-atherogenic agent in the vascular system. Vitexin, a flavonoid, has gained attention for its extensive vasculoprotective effects. The aim of this study was to explore the effect of vitexin on eNOS and NO synthesis in human umbilical vein endothelial cells (HUVECs). Cultured HUVECs were assigned to four distinct groups: control, oxidative stress induced by 180 μM hydrogen peroxide (H2O2), treatment with 300 μM vitexin, and simultaneous treatment with H2O2 and vitexin. After 24 h, HUVECs were harvested and the mRNA expression, protein levels and activity of eNOS were measured. Additionally, NO levels were determined. The study findings showed that the HUVECs treated with vitexin demonstrated an enhanced NO production compared to the control group. Vitexin facilitated production of NO in HUVECs by upregulating the expression of the eNOS gene, promoting eNOS protein synthesis, and increasing eNOS activity. In conclusion, vitexin enhances endothelial function by stimulating endothelial NO production by eNOS, suggesting its potential as a therapeutic agent for vascular health.